Synthesis and in vivo anti-ulcer evaluation of some novel piperidine linked dihydropyrimidinone derivatives - Mashooq Ahmad Bhat; Mohamed A. Al-Omar; Ahmed M. Naglah (Taylor & Francis Group, 2018)
Dihydropyrimidinone derivatives containing piperidine moiety were synthesised in a good yield. All the compounds were confirmed by elemental analysis and spectral data. Anti-ulcer activity of novel dihydropyrimidinone-piperidine hybrids (1-18) was evaluated. Among them, four compounds (3, 8, 11 and 15) were found to be most active in 80% ethanol-induced ulcer experimental animal model. All the potent compounds were further evaluated for anti-ulcer activity by different in vivo anti-ulcer models to study the effect of compounds on anti-secretory and cytoprotective activities. All the active compounds inhibited the formation of gastric ulcers and increased the formation of gastric mucin secretion. Compound 15 was found to be the most potent compound of the series as anti-ulcer agent. Additional experimental studies on lead compound 15 will result in a new class of orally active molecule for anti-ulcer activity.